ANALISIS ESTETIKA FOTO JURNALIS KARYA ABRIAWAN ABHE: STUDI KASUS FOTO PON XX PAPUA TAHUN 2021 - Fausan, Fahril; B. Pasyah, Soekarno; Kadir, Irsan (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
This research aims to analyze the aesthetics of photojournalism works by Abriawan Abhe, with a case study on the photos of PON XX Papua in 2021. Using the method of visual content analysis, the photos were evaluated to identify aesthetic elements such as composition, lighting, color, contrast, and other photographic techniques. The findings reveal that Abriawan Abhe successfully creates aesthetically pleasing and captivating photojournalistic images with strong composition, appropriate lighting, thoughtful color choices, and diverse photographic techniques. In addition to providing information about the event, these photos also possess a strong artistic value, offering a deeper understanding of the aesthetics of photojournalism and contributing to the appreciation of aesthetic qualities in impactful and engaging photojournalistic works.